2015
DOI: 10.1001/jamapsychiatry.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Functional Connectivity Within and Between Frontostriatal Circuits and Its Association With Compulsive Drug Use and Trait Impulsivity in Cocaine Addiction

Abstract: IMPORTANCE Converging evidence has long identified both impulsivity and compulsivity as key psychological constructs in drug addiction. Although dysregulated striatal-cortical network interactions have been identified in cocaine addiction, the association between these brain networks and addiction is poorly understood. OBJECTIVES To test the hypothesis that cocaine addiction is associated with disturbances in striatal-cortical communication as captured by resting-state functional connectivity (rsFC), measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
153
2
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(180 citation statements)
references
References 63 publications
24
153
2
1
Order By: Relevance
“…This reduced functional coupling between the ventral striatum and dACC is consistent with previous findings. Intrinsic connectivity of the ventral striatum-dACC has been shown to be associated with greater severity of nicotine (59) and cocaine addiction (60). Also, Crane et al (61) have reported that the high-risk group in alcohol-use disorder (i.e., binge drinkers) have difficulty engaging this network during reward processing.…”
Section: Discussionmentioning
confidence: 99%
“…This reduced functional coupling between the ventral striatum and dACC is consistent with previous findings. Intrinsic connectivity of the ventral striatum-dACC has been shown to be associated with greater severity of nicotine (59) and cocaine addiction (60). Also, Crane et al (61) have reported that the high-risk group in alcohol-use disorder (i.e., binge drinkers) have difficulty engaging this network during reward processing.…”
Section: Discussionmentioning
confidence: 99%
“…While the functional connectivity of these circuits in cocainedependent individuals has been measured in a resting state Hu et al, 2015;Li et al, 2000;Tomasi et al, 2010), the goal of this study was to investigate the functional connectivity in these circuits when they were engaged by an external source. The primary results demonstrate that (1) ventral striatal areas responsible for limbic arousal are not as responsive to the same level of medial prefrontal stimulation in cocaine users as controls (consistent with opponent process theory), (2) dorsal striatal areas typically implicated in cognitive control and habit formation have similar response profiles in cocaine users and controls, and (3) the reciprocal relationship between DLPFC stimulation and Brodmann 10 (MPFC) attenuation observed in controls is disrupted in cocaine users.…”
Section: Discussionmentioning
confidence: 99%
“…This was motivated by the knowledge that cocaine users appear to have a very low neural response to natural rewards (Cheetham et al, 2010), which typically engage the limbic system (eg the ventral MPFC, ACC, and striatum) (Asensio et al, 2010a;Kelley and Berridge, 2002). In addition, several resting state functional MRI studies have demonstrated lower baseline resting state functional connectivity with the MPFC in cocaine users Gu et al, 2007;Tomasi et al, 2010), though other studies have demonstrated that cocaine users have higher connectivity in these circuits (Camchong et al, 2011;Hu et al, 2015). The present study demonstrated that left frontal pole stimulation in the controls led to an increase in BOLD signal in a network of limbic regions including the caudate, parahippocampal gyrus, and the amygdala.…”
Section: Ventral Medial Prefrontal Cortex: Impaired Mobilization In Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Rs-fMRI involves analysis of spontaneous brain function using blood oxygen level-dependent contrasts in the absence of a task, rendering it suitable for clinical applications [11]. Rs-fMRI has been successfully applied to the characterization of brain function disturbances in substance-dependent populations, including individuals addicted to heroin [12][13][14][15], nicotine [16][17][18][19], and cocaine [20,21]. These rs-fMRI findings provide evidence that regions related to reward, memory and learning, cognitive control, motivation, and salience evaluation are involved in addiction [22].…”
Section: Introductionmentioning
confidence: 99%